Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Sarah Ann Prince, mother of Estelle Watkins Morgan, and wife of William Bravel Watkins Sarah and William Watkins are paternal grandparents of William Riley Watkins, former District Rep for Assemblymember Jim Costa